Two Celebrated Classical Problems in Geometric Constructions - Radhiah Radhiah (Department of Mathematics, Hasanuddin University, 2020)
The main topic of this paper is about two celebrated classical problems in geometric constructions where the only allowed instruments are compass and ruler with no scale. Two such problems are (1) trisecting an angle, and (2) doubling the cube. In addition, we also study about the construction of 7-gon and 10-gon.